FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BERWIRAUSAHA SISWA SMK NASIONAL PELALAWAN - Lisa Lusiana; Gimin Gimin; Sumarno Sumarno (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the factors that influence the interest in entrepreneurship in Pelalawan National Vocational School students. The population in this study were all students of Pelalawan National Vocational School, amounting to 192 students from class X, XI, and XII. The sample was taken using the Stratified random sampling technique, which was 66 students. Data was collected using questionnaires, data analysis using descriptive analysis and multiple linear regression. Descriptively, interest in entrepreneurship in students is included in the low category, confidence is included in the low category, creativity is included in the low category, and risk taking is included in the low category. Factors of confidence, creativity, and courage to take risks have a significant effect on the interest in entrepreneurship with the regression equation Y = 0.954 + 0.242X1 + 0.293X2 + 0.278X3 and contribute to the interest in student entrepreneurship by 23.6%.Key Words: Confidence, Creativity, Dare to Take Risks and Interest in Entrepreneurship.